Anmeldelser - Kirkegaard, Annemette (Danish Yearbook of Musicology, 2004)
Review of: Johannes Brusila: ‘Local music, not from here’. The Discourse of World Music examined through three Zimbabwean case studies: The Bhundu Boys, Virginia Mukwesha and Sunduza (Finnish Society for Etnomusicology Publ., 10), Helsinki: Finnish Society for Etnomusicology, 2003